Temporal patterning of the vertebrate developing neural tube - Sagner, Andreas (Current Opinion in Genetics & Development, 2024)
The chronologically ordered generation of distinct cell types is essential for the establishment of neuronal diversity and the formation of neuronal circuits. Recently, single-cell transcriptomic analyses of various areas of the developing vertebrate nervous system have provided evidence for the existence of a shared temporal patterning program that partitions neurons based on the timing of neurogenesis. In this review, I summarize the findings that lead to the proposal of this shared temporal program before focusing on the developing spinal cord to discuss how temporal patterning in general and this program specifically contributes to the ordered formation of neuronal circuits.
CRIS-Team Scopus Importer:2024-03-22